The Influence of Work Life Balance (WLB) and Work Motivation on the Efficiency and Satisfaction of the Utilization Integrated Dynamic Archive Information System (SRIKANDI) (Case Study at the Regional Plantation Service of West Celebes Province) - Muhammad, Azhary Bahar; Nohong, Mursalim (Scientia Integritas Utama, 2022)
The purpose of this research is to examine the effects of work-life balance (WLB) and motivation on the effectiveness and satisfaction of the use of the Integrated Dynamic Archive Information System (SRIKANDI) at the West Celebes Province Regional Plantation Service. This study is quantitative and descriptive in nature. Saturated sampling was used to sample the population of this study, which consisted of 72 State Civil Service (ASN) respondents who were all members of the Regional Plantation Service of West Celebes Province. Questionnaires were sent as part of the data gathering process, and path analysis was employed for data analysis. According to the study's findings, there are several factors that affect employee work performance: (1) work load bias (WLB); (2) work motivation; (3) work load bias (WLB) on satisfaction when using the SRIKANDI application; (4) work motivation on satisfaction when using the SRIKANDI application; (5) work efficiency on satisfaction when using the SRIKANDI application; (6) work motivation on job satisfaction through work efficiency as an intervening variable; and (7) work load bias (WLB) on employee job satisfaction through employee work efficiency as an intervening variable.